Financial Analysis of Production Cost of Chocolate Drinks Using Cocoa Butter Substituted from Palm Oil - Nurdelima Gulo; Fitriana (Faculty of Economics and Business, University of Pancasakti Tegal, 2024)
CBS (Cocoa Butter Substitute) or commonly known as cocoa butter substitute fat is obtained from the process of modifying palm kernel oil by hydrogenation so that its characteristics are physically similar to CB. Chocolate products in their manufacture require fat which is usually obtained from cocoa butter. However, cocoa butter is usually difficult to obtain and more expensive in terms of price, so CBS is used as a substitute for CB. This study aims to determine the level of financial feasibility and analyze the sensitivity aspect in the manufacture of industrial-scale chocolate beverage products. The feasibility criteria in this study are the calculation of NPV, IRR, Net B / C, PP and Sensitivity using Ms. Office Excel. Based on the results of the calculation of the financial aspect with an interest of 10%, it meets the requirements and is feasible with the NPV value generated within a period of 10 years of Rp. 892,138,919,349-, with a production capacity of 25 tons per day with a packaging weight of 1000gr, 5000gr and 25000 gr respectively. The IRR value obtained was 94.97% where the IRR value was greater than the interest of 10%. The Net B/C obtained is Rp. 9.45 with a payback period of 1.6 years. The results of the sensitivity analysis show that a decrease in selling price, an increase in raw materials and an increase in operational costs of 20% have a significant impact on business feasibility.